Tax Planning Among Companies in Malaysia in an E-Commerce Environment - Jaafar Sidik, Morni Hayati (2010)
E-commerce poses new way of doing business and provide new opportunities for companies to broaden their markets. E-commerce transactions, however, have raised several tax problems. One of them is the ambiguities surrounding the concept of permanent establishment. These ambiguities, on the other hand, may be used by e-commerce companies to reduce tax burden through tax planning. The purpose of this study is to examine the tax planning from PE interpretation in e-commerce environment in the Malaysian context. This study employed two types of data collection methods. The first method is the quantitative data collection through questionnaire survey. Nine hundred and fifty questionnaires were sent to the selected respondents using both postal and electronic mail (e-mail). Out of 950 copies distributed, 107 questionnaires were received from the respondents. The second method involved collecting qualitative data through in-depth interviews. The key personnel from four e-commerce companies were interviewed to gain further insights on their tax planning. The results of this study showed that 95 percent of the respondents are tax planning adopters. The statistical analyses revealed that although the respondents adopt tax planning in e-commerce environment, they do not depend on the use of tax consultants, organizational characteristics and innovation factors. The study also showed that there is no relationship between website address and tax planning adoption. Apart from that, there was no clear relationship between tax planning adoption and tax planning perceptions. The findings suggest that even though the companies adopt tax planning, it does not mean that they perceive tax planning to be important. In summary, the findings suggest that tax issues might not be the main consideration when a company in Malaysia plans their website. There are other issues that are more important than tax issues such as legal and securities issues. This implies that the tax authorities in Malaysia may have ample time to study their tax policy in e-commerce environment. At the same time, CEOs and managers of the e-commerce companies should ensure they are equipped with tax knowledge in order to avoid any unnecessary tax liabilities.